HUBUNGAN PROGRAM ADIWIYATA TERHADAP PENDIDIKAN AGAMA ISLAM BERWAWASAN KARAKTER - Rizki Amelia, Ikhfi; Mutmainnah, Rofikasari (Al-Misbah (Jurnal Islamic Studies), 2019)
The environment is a set of parts with all the substance, effort, nature and inhabitants of the world, including human beings and their behavior that controls the life and peace of humans and other living things. The current natural problems are very alarming, lack of awareness, knowledge, understanding and ignorance so that they do not do, do not do, pretend not to know, do not like to read, even the other most dangerous cause is a greedy temperament that wants to find its own benefits. All of these cause environmental damage. With the existence of the adiwiyata program, the school population is obliged to preserve and preserve environmental knowledge through the principle of running an efficient school to uphold sustainable development. This study aims to determine the relationship of the adiwiyata program to environmental character education. The questions to be answered through this research are: 1. The adiwiyata program at MAN 1 Jombang. 2. Character education care for the environment at MAN 1 Jombang. 3. How is the relationship between the adiwiyata program and environmental education character education. This study uses a type of field correlation research. The approach used in this research is a quantitative approach. The design of this study was expost facto. Researchers took a sample of 60 respondents from 6 classes each class taken 10 people randomly. Hypothesis testing in this study uses the Spearman correlation. Thus, the researcher tried to explain the relationship between the adiwiyata program and environmental care character education at MAN 1 Jombang. From the analysis it was found that known sig of 0,000 (sig <0.05), means that H0 is rejected and HA is accepted. This means that there is a relationship between variable X (Adiwiyata Program) and Y (Environmental Care Character). Then it is also known that the coefficient value is 0.940 (positive value), which means a positive correlation (proportional), where the greater X then Y is also greater.